Antecedents of Tax Awareness and The Implementation of Samsat Drive-Thru Services Towards Compliance Motor Vehicle Taxpayers - Oktarini , Rahmi Dwi; Tripermata, Lukita; Munandar, Aris (Manunggal Halim Jaya, 2025)
The tax system in Indonesia continues to evolve to enhance taxpayer compliance. The government strives to provide various more effective policies and services, one of which is through the Samsat Drive Thru innovation. This study focuses on factors that influence tax awareness and examines the impact of the Samsat Drive Thru service on the level of compliance of motor vehicle taxpayers at the UPTB Samsat Palembang 1. Sampling was conducted using the Slovin method to obtain 99 respondents, while the research approach used was quantitative. The collected data were analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) technique. The results of the study indicate that tax awareness has a significant influence on increasing motor vehicle taxpayer compliance. Taxpayers with a high level of awareness tend to be more compliant in fulfilling their obligations on time. Additionally, the implementation of the Samsat Drive Thru service has been proven to increase the efficiency of tax payments by streamlining the service process and standardizing administrative procedures. However, the effectiveness of this service is still influenced by several other factors, including the application of tax sanctions, socialization policies, and the ease of accessing the service. The findings of this study offer valuable insights for the government in designing more effective tax policies. More inclusive service innovations and improved tax education are needed to maximize regional tax revenue. Furthermore, strengthening infrastructure and leveraging technology are crucial aspects of building a more modern and efficient tax system.